Method for manufacturing polarizing plates

JP7933486B2Active Publication Date: 2026-10-13SUMITOMO CHEM CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2021179548
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-02
Publication Date
2026-10-13
Estimated Expiration
2041-11-02

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、偏光子の両側に積層される保護フィルムの温度40℃、相対湿度90%RHにおける透湿度がいずれも200g/m2·24hr以下である偏光板であって、保護フィルムと水系接着剤層との間の密着性および外観品質が良好である偏光板およびその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933486000003
    Figure 0007933486000003
  • Figure 0007933486000004
    Figure 0007933486000004
  • Figure 0007933486000005
    Figure 0007933486000005
Patent Text Reader

Abstract

To provide a polarizing plate in which both protective films laminated on both sides of the polarizer must have a moisture permeability of 200 g / m2 / 24hr or less at a temperature of 40°C and a relative humidity of 90%RH and which has good appearance quality and adhesion between the protective film and aqueous adhesive layer and to provide its production method.SOLUTION: A polarizing plate includes a first protective film, a polarizer, and a second protective film. The first protective film and the polarizer are bonded through a first aqueous adhesive layer. The second protective film and the polarizer are bonded through a second aqueous adhesive layer. Both the first protective film and the second protective film have a moisture permeability of 200 g / m2 / 24hr or less at a temperature of 40°C and a relative humidity of 90%RH.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to polarizing plates, and more particularly to methods for manufacturing polarizing plates. [Background technology]

[0002] Patent Document 1 proposes a polarizing plate in which a polarizer and a protective film are bonded together via a water-based adhesive. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2003-211589 [Overview of the project] [Problems that the invention aims to solve]

[0004] In a polarizing plate in which protective films are bonded to both sides of the polarizer via a water-based adhesive, if the moisture permeability of the protective films bonded to both sides is low, sufficient adhesion between the protective films and the water-based adhesive layer may not be achieved.

[0005] In polarizing plates in which protective films are bonded to both sides of the polarizing plate via an ultraviolet-curing adhesive, if the protective films bonded to both sides contain an ultraviolet absorber, sufficient adhesion between the protective film and the ultraviolet-curing adhesive layer may not be achieved. Furthermore, when bonding a thin protective film to a polarizer using an ultraviolet-curing adhesive, wrinkles can form in the protective film due to the curing shrinkage of the adhesive, which can impair the appearance quality of the polarizer.

[0006] In this invention, the protective film laminated to both sides of the polarizer has a moisture permeability of 200 g / m² at a temperature of 40°C and a relative humidity of 90% RH. 2The objective is to provide a polarizing plate with a shelf life of 24 hours or less, which exhibits good adhesion between the protective film and the water-based adhesive layer, as well as good appearance quality, and a method for manufacturing the same. [Means for solving the problem]

[0007] The present invention provides the following polarizing plates and methods for manufacturing polarizing plates. [1] comprising a first protective film, a polarizer, and a second protective film, The first protective film and the polarizer are bonded together via a first aqueous adhesive layer. The second protective film and the polarizer are bonded together via a second aqueous adhesive layer. The moisture permeability of both the first and second protective films at a temperature of 40°C and a relative humidity of 90%RH is 200 g / m². 2 • Polarizing plates with a shelf life of 24 hours or less. [2] A polarizing plate in which the light transmittance of the first protective film and the second protective film at a wavelength of 380 nm is 10% or less. [3] The polarizing plate according to [1] or [2], wherein the adhesion between the second water-based adhesive layer and the second protective film is 0.3 N or more. [4] A first step of bonding the first protective film and the polarizer via the first aqueous adhesive layer to obtain a laminate, A second step of forming a water-based adhesive coating on the polarizer of the laminate, A third step involves drying the coating film of the aforementioned water-based adhesive to form a second water-based adhesive layer, A fourth step involves applying a surface activation treatment to the surface of the second aqueous adhesive layer opposite to the polarizer side, and then bonding the laminate and the second protective film via the second aqueous adhesive layer. They are provided in this order, The moisture permeability of both the first and second protective films at a temperature of 40°C and a relative humidity of 90%RH is 200 g / m². 2 A method for manufacturing polarizing plates, which takes less than 24 hours. [5] The method for producing a polarizing plate according to [3], further comprising a curing step of heating the polarizing plate after the fourth step. [6] The third step includes: a step of laminating a release film on the coating film of the water-based adhesive, and a step of peeling the release film after drying the coating film of the water-based adhesive, the method for producing a polarizing plate according to [4] or [5], further comprising these steps. [Advantageous Effects of Invention]

[0008] According to the present invention, it is possible to provide a polarizing plate in which the moisture permeability at a temperature of 40°C and a relative humidity of 90%RH of each of the protective films laminated on both sides of a polarizer is 200 g / m 2 ·24hr or less, and which has good adhesion between the protective film and the water-based adhesive layer and good appearance quality, as well as a method for producing the same. [Brief Description of Drawings]

[0009] [Figure 1] It is a schematic cross-sectional view showing an example of the layer configuration of the polarizing plate of the present invention. [Figure 2] It is a schematic cross-sectional view showing an example of the method for producing a polarizing plate of the present invention. [Figure 3] The appearance observation image of the surface of the polarizing plate of Example 1 is shown. [Figure 4] The appearance observation image of the surface of the polarizing plate of Comparative Example 9 is shown. [Mode for Carrying Out the Invention]

[0010] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiments. In all the following drawings, the scale of each component is appropriately adjusted for easy understanding, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.

[0011] <Polarizing Plate> The polarizing plate of the present invention comprises a first protective film, a polarizer, and a second protective film. The first protective film and the polarizer are bonded together via a first aqueous adhesive layer, and the second protective film and the polarizer are bonded together via a second aqueous adhesive layer. The moisture permeability of both the first and second protective films at a temperature of 40°C and a relative humidity of 90%RH is 200 g / m². 2 • Less than 24 hours. Hereafter, the term "protective film" may be used as a general term for both the first protective film and the second protective film. Also, "laminated" means that the two layers are in contact with each other and are bonded together.

[0012] The polarizing plate of the present invention will be described with reference to Figure 1. The polarizing plate 10 shown in Figure 1 comprises a first protective film 11, a first aqueous adhesive layer 12, a polarizer 13, a second aqueous adhesive layer 14, and a second protective film 15. The first protective film 11 and the first aqueous adhesive layer 12 may be bonded to each other in contact. The first aqueous adhesive layer 12 and the polarizer 13 may be bonded to each other in contact. The polarizer 13 and the second aqueous adhesive layer 14 may be bonded to each other in contact. The second aqueous adhesive layer 14 and the second protective film 15 may be bonded to each other in contact. Although not shown, the polarizing plate 10 may further have layers other than those shown in Figure 1, such as a bonding layer, an optical functional layer, a protective film, a front plate, and a touch panel. The polarizing plate may be a linear polarizing plate, or a circular polarizing plate in which a phase difference layer described later is laminated on a linear polarizing plate.

[0013] The moisture permeability of both the first protective film 11 and the second protective film 15 at a temperature of 40°C and a relative humidity of 90%RH is 200 g / m². 2 • Less than 24 hours. The inventors have determined that the moisture permeability of the protective film at a temperature of 40°C and a relative humidity of 90%RH is 200 g / m². 2·24hr or less, it has been found that when the water-based adhesive is dried, moisture is not sufficiently removed from the water-based adhesive, resulting in insufficient curing of the water-based adhesive, and as a result, sufficient adhesion between the polarizer and the protective film cannot be obtained. The polarizing plate 10 of the present invention tends to have excellent interlayer adhesion even though the first protective film 11 and the second protective film 15 have low moisture permeability within the above range. In addition, the polarizing plate 10 of the present invention tends to have superior appearance quality as compared with the case where an ultraviolet curable adhesive is used.

[0014] The moisture permeability of each of the first protective film 11 and the second protective film 15 at a temperature of 40°C and a relative humidity of 90%RH is, for example, 200g / m 2 ·24hr or less, and may be 150g / m 2 ·24hr or less, or 100g / m 2 ·24hr or less. The moisture permeability of each of the first protective film 11 and the second protective film 15 at a temperature of 40°C and a relative humidity of 90%RH is, for example, 1g / m 2 ·24hr or more, preferably 10g / m 2 ·24hr or more, more preferably 50g / m 2 ·24hr or more. The moisture permeability of the first protective film 11 and the second protective film 15 at a temperature of 40°C and a relative humidity of 90%RH may be the same or different. The moisture permeability at a temperature of 40°C and a relative humidity of 90%RH can be measured according to the method described in the section of Examples below.

[0015] In the polarizing plate 10, the adhesion between the second water-based adhesive layer 14 and the second protective film 15 may be, for example, 0.1N / 25mm or more, may be 0.3N / 25mm or more, preferably 0.5N / 25mm or more, and more preferably 1.0N / 25mm or more. In the polarizing plate 10, the adhesion between the second water-based adhesive layer 14 and the second protective film 15 is usually 20N / 25mm or less, and may be, for example, 15N / 25mm or less or 10N / 25mm or less. The adhesion force between the first aqueous adhesive layer 12 and the first protective film 11 of the polarizing plate 10 is typically 0.1 N / 25 mm or more and 20 N / 25 mm or less. The adhesion force can be measured according to the method described in the Examples section below.

[0016] (Protective film) The first protective film 11 and the second protective film 15 may have the function of protecting the polarizer 13, in particular the function of protecting the surface of the polarizer 13. The first protective film 11 is bonded to one side of the polarizer 13 via a first aqueous adhesive layer 12. The second protective film 15 is bonded to one side of the polarizer 13 via a second aqueous adhesive layer 14.

[0017] The first protective film 11 and the second protective film 15 can be films made of a light-transmitting (preferably optically transparent) thermoplastic resin, such as polyolefin resins like chain polyolefin resins (polypropylene resins, etc.) and cyclic polyolefin resins (norbornene resins, etc.); cellulose resins like triacetylcellulose and diacetylcellulose; polyester resins like polyethylene terephthalate and polybutylene terephthalate; polycarbonate resins; (meth)acrylic resins like methyl methacrylate resins; polystyrene resins; polyvinyl chloride resins; acrylonitrile-butadiene-styrene resins; acrylonitrile-styrene resins; polyvinyl acetate resins; polyvinylidene chloride resins; polyamide resins; polyacetal resins; modified polyphenylene ether resins; polysulfone resins; polyethersulfone resins; polyarylate resins; polyamide-imide resins; polyimide resins, etc.

[0018] Examples of chain-like polyolefin resins include homopolymers of chain-like olefins such as polyethylene resin (a homopolymer of ethylene, or a copolymer mainly composed of ethylene) and polypropylene resin (a homopolymer of propylene, or a copolymer mainly composed of propylene), as well as copolymers composed of two or more chain-like olefins.

[0019] Cyclic polyolefin resins are a general term for resins polymerized using cyclic olefins as polymerization units, and examples include resins described in Japanese Patent Publication No. 1-240517, Japanese Patent Publication No. 3-14882, and Japanese Patent Publication No. 3-122137. Specific examples of cyclic polyolefin resins include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers of cyclic olefins with chain-like olefins such as ethylene and propylene (typically random copolymers), graft polymers modified with unsaturated carboxylic acids or their derivatives, and their hydrides. Among these, norbornene resins using norbornene monomers such as norbornene and polycyclic norbornene monomers as the cyclic olefin are preferred.

[0020] Polyester resins, excluding the cellulose ester resins described below, are resins containing ester bonds and are generally composed of polycondensates of polycarboxylic acids or their derivatives and polyhydric alcohols. Divalent dicarboxylic acids or their derivatives can be used as polycarboxylic acids or their derivatives, such as terephthalic acid, isophthalic acid, dimethyl terephthalate, and dimethyl naphthalenedicarboxylate. Divalent diols can be used as polyhydric alcohols, such as ethylene glycol, propanediol, butanediol, neopentyl glycol, and cyclohexanedimethanol. A typical example of a polyester resin is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol.

[0021] (Meth)acrylic resins are resins whose main constituent monomers are compounds having a (meth)acryloyl group. Specific examples of (meth)acrylic resins include, for example, poly(meth)acrylic acid esters such as polymethyl methacrylate; methyl methacrylate-(meth)acrylic acid copolymers; methyl methacrylate-(meth)acrylic acid ester copolymers; methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymers; (meth)acrylic acid-styrene copolymers (MS resin, etc.); and copolymers of methyl methacrylate and compounds having an alicyclic hydrocarbon group (for example, methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylic acid copolymer, etc.). Preferably, poly(meth)acrylic acid C such as poly(meth)acrylate 1-6 A polymer mainly composed of alkyl esters is used, and more preferably, a methyl methacrylate resin mainly composed of methyl methacrylate (50% to 100% by mass, preferably 70% to 100% by mass) is used.

[0022] Cellulose ester resins are esters of cellulose and fatty acids. Specific examples of cellulose ester resins include cellulose triacetate, cellulose diacetate, cellulose trippropionate, and cellulose dipropionate. Also included are copolymers of these, and those in which some of the hydroxyl groups are modified with other substituents. Among these, cellulose triacetate (triacetylcellulose) is particularly preferred.

[0023] Polycarbonate resins are engineering plastics composed of polymers in which monomer units are bonded together via carbonate groups.

[0024] The light transmittance of both the first protective film 11 and the second protective film 15 at a wavelength of 380 nm can be 10% or less. In polarizing plates in which protective films are bonded to both sides of the polarizer via an ultraviolet-curable adhesive, if the protective films bonded to both sides contain an ultraviolet absorber, sufficient adhesion between the protective film and the ultraviolet-curable adhesive layer may not be obtained. The polarizing plate of the present invention tends to have excellent interlayer adhesion even when the light transmittance of both protective films arranged on both sides of the polarizer at a wavelength of 380 nm is 10% or less. The light transmittance can be measured according to the method described in the Examples section below.

[0025] The light transmittance of the first protective film 11 and the second protective film 15 at a wavelength of 380 nm may both be, for example, 5% or less, 0% or more, or 3% or more. The light transmittance of the first protective film 11 and the second protective film 15 at a wavelength of 380 nm may be the same or different.

[0026] The thickness of the first protective film 11 and the second protective film 15 is usually 1 μm to 100 μm, but from the viewpoint of reducing the thickness of the polarizing plate after lamination, and from the viewpoint of strength and handling, it is preferable that it be 5 μm to 60 μm, more preferably 5 μm to 40 μm, and even more preferably 10 μm to 20 μm. Furthermore, the polarizing plate of this embodiment tends to have excellent appearance quality even when the thickness of the protective film is thin.

[0027] The first protective film 11 and the second protective film 15 may have a phase difference function for purposes such as viewing angle compensation. In this case, the film itself may have a phase difference function, or it may have a separate phase difference layer, or a combination of both.

[0028] The protective film may have ultraviolet (UV) absorption properties for purposes such as improving the light resistance of the polarizing plate. In this case, the film itself may have UV absorption properties, or it may have a separate UV absorption layer, or a combination of both. Even when the protective film has UV absorption properties, good adhesion can be achieved.

[0029] The first protective film 11 and the second protective film 15 may be made of the same type of thermoplastic resin or of different types of thermoplastic resin. They may also have the same or different thicknesses. Furthermore, they may have the same or different phase difference characteristics.

[0030] At least one of the protective films may have a surface treatment layer (coating layer) on its outer surface (the side opposite to the polarizer), such as a hard coat layer, anti-glare layer, light diffusion layer, anti-reflective layer, low refractive index layer, anti-static layer, or anti-fouling layer. The thickness of the protective film includes the thickness of the surface treatment layer.

[0031] (First water-based adhesive layer) The first aqueous adhesive layer 12 can be placed between the first protective film 11 and the polarizer 13 in order to bond them together. The first aqueous adhesive layer 12 may be a single layer or a multi-layer layer.

[0032] The first aqueous adhesive layer 12 can be formed from an aqueous adhesive. Examples of aqueous adhesives include adhesives made from an aqueous solution of polyvinyl alcohol resin and aqueous two-component urethane emulsion adhesives. Among these, aqueous adhesives made from an aqueous solution of polyvinyl alcohol resin are preferably used. As the polyvinyl alcohol resin, vinyl alcohol homopolymers obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as polyvinyl alcohol copolymers obtained by saponifying a copolymer of vinyl acetate and other monomers copolymerizable thereto, or modified polyvinyl alcohol polymers obtained by partially modifying the hydroxyl groups thereof. The aqueous adhesive may contain crosslinking agents such as aldehyde compounds (glyoxal, etc.), epoxy compounds, melamine compounds, methylol compounds, isocyanate compounds, amine compounds, and polyvalent metal salts.

[0033] The content of polyvinyl alcohol-based resin in the aqueous solution of polyvinyl alcohol-based resin may be, for example, 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of water, preferably 1.5 parts by mass or more and 10 parts by mass or less, and more preferably 2.5 parts by mass or more and 5 parts by mass or less.

[0034] The first water-based adhesive layer 12 can be formed by laminating the first protective film 11 and the polarizer 13 via a water-based adhesive, and then performing a drying step to remove the water contained in the water-based adhesive. The first water-based adhesive layer 12 is formed when the water-based adhesive dries, and the first protective film 11 and the polarizer 13 are bonded together. After the drying step, a curing step may be provided to cure the laminate having a layered structure of the first protective film 11, the first water-based adhesive layer 12, and the polarizer 13.

[0035] The thickness of the first water-based adhesive layer 12 is preferably 0.1 μm or more and 1 μm or less.

[0036] The first water-based adhesive layer 12 and the second water-based adhesive layer 14 may use the same type of adhesive or different types, and may have the same or different thicknesses.

[0037] (Polarizer) Examples of polarizers 13 include stretched films or stretched layers on which dichroic dyes are adsorbed, and polarizer layers obtained by coating and curing dichroic dyes. When the polarizer includes a base film and an orientation film, as described later, these are collectively referred to as the polarizer.

[0038] Specifically, iodine and dichroic organic dyes are used as dichroic dyes. Examples of dichroic organic dyes include azo dyes. Azo dyes include dichroic direct dyes made from disazo compounds such as CIDIRECT RED 39, and dichroic direct dyes made from compounds such as trisazo and tetrakisazo.

[0039] (Stretched film or stretched layer with adsorbed dichroic dye) A stretched film with adsorbed dichroic dyes can typically be manufactured by a process that involves uniaxial stretching of a polyvinyl alcohol-based resin film, a process of dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dye, a process of treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dyes with an aqueous boric acid solution, and a process of washing with water after treatment with the aqueous boric acid solution. The thickness of the stretched film on which the dichroic dye is adsorbed may be, for example, 2 μm or more and 40 μm or less, and from the viewpoint of reducing the thickness of the polarizing plate after lamination, 20 μm or less, and more preferably 15 μm or less, is preferred.

[0040] Polyvinyl alcohol-based resins are obtained by saponifying polyvinyl acetate-based resins. Polyvinyl acetate-based resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate with other monomers copolymerizable thereto. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having ammonium groups.

[0041] The degree of saponification of the polyvinyl alcohol-based resin is usually around 85 mol% to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol-based resin may be modified; for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol-based resin is usually 1000 to 10000, preferably 1500 to 5000.

[0042] A stretched layer with adsorbed dichroic dye can typically be manufactured by the following steps: applying a coating solution containing the polyvinyl alcohol-based resin onto a base film; uniaxially stretching the resulting laminated film; dyeing the polyvinyl alcohol-based resin layer of the uniaxially stretched laminated film with a dichroic dye to adsorb the dichroic dye and form a polarizer layer; treating the film with adsorbed dichroic dye with an aqueous boric acid solution; and washing with water after treatment with the aqueous boric acid solution. If necessary, the base film may be peeled off from the stretched layer with adsorbed dichroic dye. The material and thickness of the base film may be the same as those of the thermoplastic resin film described later.

[0043] (A polarizer layer formed by applying and curing a dichroic dye) Examples of polarizer layers obtained by coating and curing a dichroic dye include polarizer layers containing cured polymerizable liquid crystal compounds, such as a layer obtained by coating a base film with a composition containing a polymerizable liquid crystal compound and a dichroic dye, or a composition containing a polymerizable liquid crystal compound and a dichroic dye, and curing it. The base film may have an alignment film on one side. The thickness of the alignment film may be, for example, 5 nm to 1 μm.

[0044] The polarizer 13 may be incorporated into the polarizer plate 10 together with the base film, or it may be incorporated into the polarizer plate 10 after peeling off the base film from the polarizer layer, which is formed by coating and curing a dichroic dye. The material and thickness of the base film may be the same as those of the first protective film 11 described above. The base film may have a hard coat layer (HC layer) formed on at least one surface as a protective layer.

[0045] The thickness of the polarizer layer, obtained by coating and curing a dichroic dye, is usually 10 μm or less, preferably 8 μm or less, and more preferably 5 μm or less.

[0046] (Second water-based adhesive layer) The second aqueous adhesive layer 14 is placed between the polarizer 13 and the second protective film 15 and can have the function of bonding the two together. The second aqueous adhesive layer 14 may be a single layer or a multi-layer layer.

[0047] The second water-based adhesive layer 14 can be formed from a water-based adhesive. Examples and preferred ranges of water-based adhesives for forming the second water-based adhesive layer 14 are those given in the description of the first water-based adhesive layer 12.

[0048] When the adhesive forming the second aqueous adhesive layer 14 is an adhesive consisting of an aqueous solution of polyvinyl alcohol-based resin, the content of polyvinyl alcohol-based resin in the aqueous solution of polyvinyl alcohol-based resin may be, for example, 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of water, preferably 1.5 parts by mass or more and 10 parts by mass or less, and more preferably 2.5 parts by mass or more and 5 parts by mass or less.

[0049] The second water-based adhesive layer 14 can be formed by forming a coating of water-based adhesive on the polarizer 13 and then drying the coating. After forming the second water-based adhesive layer 14, the second protective film 15 can be laminated via the second water-based adhesive layer 14. After forming the second water-based adhesive layer 14, before laminating the second protective film 15, the second water-based adhesive layer 14 can be subjected to a surface activation treatment as described later. After laminating the second protective film 15, a curing step may be provided to cure the polarizer 10, for example, as described later.

[0050] The thickness of the second water-based adhesive layer 14 is preferably 0.1 μm or more and 1 μm or less.

[0051] (Bonding layer) The polarizing plate 10 may have a bonding layer on one or both sides. The bonding layer may be an adhesive layer or a bonding agent layer. The bonding layer may have the function of bonding the optical functional layer, front plate and touch panel described later to the polarizing plate 10, or bonding the polarizing plate 10 to an image display element. The polarizing plate 10 can be made into a polarizing plate with an adhesive layer by placing an adhesive layer on one side. Also, if the optical functional layer consists of two or more layers, each layer may be bonded via a bonding layer.

[0052] The adhesive layer can be composed of an adhesive composition mainly composed of resins such as (meth)acrylic resins, rubber resins, urethane resins, ester resins, silicone resins, and polyvinyl ether resins. Among these, an adhesive composition using (meth)acrylic resin as the base polymer, which has excellent transparency, weather resistance, and heat resistance, is preferred. The adhesive composition may be of the active energy ray curing type or thermosetting type. The thickness of the adhesive layer is usually 3 μm to 30 μm, preferably 3 μm to 25 μm.

[0053] As the (meth)acrylic resin (base polymer) used in the adhesive composition, polymers or copolymers using one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, are preferably used. It is preferable to copolymerize polar monomers into the base polymer. Examples of polar monomers include monomers having carboxyl groups, hydroxyl groups, amide groups, amino groups, epoxy groups, etc., such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.

[0054] The adhesive composition may contain only the above-mentioned base polymer, but usually further contains a crosslinking agent. Examples of crosslinking agents include divalent or higher metal ions that form metal carboxylate salts with carboxyl groups; polyamine compounds that form amide bonds with carboxyl groups; polyepoxy compounds or polyols that form ester bonds with carboxyl groups; and polyisocyanate compounds that form amide bonds with carboxyl groups. Among these, polyisocyanate compounds are preferred.

[0055] The thickness of the adhesive layer is preferably 1 μm to 200 μm, more preferably 2 μm to 100 μm, even more preferably 2 μm to 80 μm, and particularly preferably 3 μm to 50 μm.

[0056] Any suitable adhesive can be used to constitute the adhesive layer. Examples of adhesives that can be used include water-based adhesives and active energy ray-curing adhesives.

[0057] The thickness of the adhesive during application can be set to any appropriate value. For example, it can be set so that an adhesive layer of the desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm to 7 μm, more preferably 0.01 μm to 5 μm, even more preferably 0.01 μm to 2 μm, and most preferably 0.01 μm to 1 μm.

[0058] As a water-based adhesive, the water-based adhesives mentioned above can be used.

[0059] The above-mentioned active energy ray curing adhesive is an adhesive containing a curable compound that hardens upon irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays, and is preferably an ultraviolet-curing adhesive.

[0060] The curable compound described above can be a cationically polymerizable curable compound or a radically polymerizable curable compound. Examples of cationically polymerizable curable compounds include epoxy compounds (compounds having one or more epoxy groups in the molecule), oxetane compounds (compounds having one or more oxetane rings in the molecule), or combinations thereof. Examples of radically polymerizable curable compounds include (meth)acrylic compounds (compounds having one or more (meth)acryloyloxy groups in the molecule), other vinyl compounds having a radically polymerizable double bond, or combinations thereof. Cationically polymerizable curable compounds and radically polymerizable curable compounds may be used in combination. Active energy ray curable adhesives usually further include at least one of a cationic polymerization initiator and a radical polymerization initiator for initiating the curing reaction of the curable compound described above.

[0061] To enhance adhesion, a surface activation treatment may be applied to the bonding surface of at least one of the adhesive layer and the layer to be bonded to the adhesive layer. Examples of surface activation treatments include dry treatments such as corona treatment, plasma treatment, electrical discharge treatment (glow discharge treatment, etc.), ozone treatment, UV ozone treatment, and ionizing ray treatment (ultraviolet treatment, electron beam treatment, etc.). These surface activation treatments may be performed individually or in combination of two or more.

[0062] (optical functional layer) The optical functional layer can be, for example, a phase difference layer. Examples of phase difference layers include a layer that provides a phase difference of λ / 2, a layer that provides a phase difference of λ / 4 (positive A plate), and a positive C plate. The optical functional layer may include an alignment film and a substrate, or it may have two or more liquid crystal layers, alignment films, and substrates. If the polarizing plate 10 has a film that provides a phase difference of λ / 4, the polarizing plate 10 can be a circular polarizer. The protective film can also serve as the phase difference layer, but the phase difference layer can also be laminated separately from these films. In the latter case, the phase difference layer can be laminated onto the polarizing plate 10 via the aforementioned bonding layer.

[0063] Examples of the phase difference layer include a birefringent film composed of a stretched film of a translucent thermoplastic resin, and the above-mentioned liquid crystal layer formed on a base film. The base film is usually a film made of a thermoplastic resin, and an example of a thermoplastic resin is a cellulose ester resin such as triacetylcellulose.

[0064] Other examples of optical functional layers include light-gathering plates, brightness-enhancing films, reflective layers (reflective films), semi-transparent reflective layers (semi-transparent reflective films), light-diffusing layers (light-diffusing films), and anti-reflective films.

[0065] (Protective film) The polarizing plate 10 can be made into a polarizing plate with a protective film by laminating a protective film onto its surface (typically the surface of the hard coat layer or protective film). The protective film is peeled off along with its adhesive layer after the polarizing plate 10 has been bonded to, for example, an image display element or other optical component.

[0066] A protective film is composed, for example, of a base film and an adhesive layer formed on it. The above description is used to refer to the adhesive layer. The resin constituting the base film can be a thermoplastic resin such as polyethylene resin; polypropylene resin; polyester resin such as polyethylene terephthalate or polyethylene naphthalate; or polycarbonate resin. Preferably, it is a polyester resin such as polyethylene terephthalate.

[0067] The thickness of the protective film is not particularly limited, but it is preferably in the range of 20 μm to 200 μm. When the thickness of the substrate is 20 μm or more, the polarizing plate 10 tends to be more easily strengthened.

[0068] (Front plate) A front panel having appropriate mechanical strength and thickness is used. Examples of such front panels include transparent resin plates such as polyimide resin, acrylic resin, or polycarbonate resin, or glass plates. Functional layers such as an anti-reflective layer may be laminated on the viewing side of the front panel. Furthermore, if the front panel is a transparent resin plate, a hard coat layer may be laminated to increase physical strength, or a low moisture permeability layer may be laminated to reduce moisture permeability. The front panel can be laminated to the viewing side of the polarizing plate 10 when the polarizing plate 10 is laminated to the image display device.

[0069] (Touch panel) Various types of touch panels can be used, including resistive, capacitive, optical, and ultrasonic touch panels, as well as glass plates or transparent resin plates equipped with touch sensor functions. When a capacitive touch panel is used as the transparent component, it is preferable to provide a front panel made of glass or transparent resin plate further on the viewing side than the touch panel.

[0070] (Uses of polarizing plates) The polarizing plate 10 can be used in an image display device. The image display device is not particularly limited and can include, for example, an organic electroluminescent (organic EL) display device, an inorganic electroluminescent (inorganic EL) display device, a liquid crystal display device, a touch panel display device, a field emission display device, etc. The polarizing plate 10 can be placed on the viewing side (front side) or the back side of the image display device.

[0071] <Method for manufacturing polarizing plates> The present invention provides a method for manufacturing a polarizing plate, comprising the following steps in order: a first step of bonding a first protective film and a polarizer via a first aqueous adhesive layer to obtain a laminate; a second step of forming a coating of aqueous adhesive on the polarizer of the laminate; a third step of drying the coating of aqueous adhesive to form a second aqueous adhesive layer; and a fourth step of applying a surface activation treatment to the surface of the second aqueous adhesive layer opposite to the polarizer side, and then bonding the laminate and the second protective film via the second aqueous adhesive layer. The moisture permeability of both the first and second protective films at a temperature of 40°C and a relative humidity of 90%RH is 200g / m². 2 • Less than 24 hours. The descriptions of the first protective film 11, first water-based adhesive layer 12, polarizer 13, second water-based adhesive layer 14, and second protective film 15 in the polarizing plate 10 described above apply to the first protective film, polarizer, first water-based adhesive layer 12, polarizer 13, second water-based adhesive layer 14, and second protective film 15, respectively.

[0072] The inventors have determined that the moisture permeability of the protective film at a temperature of 40°C and a relative humidity of 90%RH is 200 g / m². 2 It has been found that if the drying time is less than 24 hours, sufficient moisture is not removed from the water-based adhesive when it is dried, resulting in insufficient curing of the water-based adhesive, and consequently, insufficient adhesion between the polarizer and the protective film. According to the polarizing plate manufacturing method of the present invention, it is possible to manufacture a polarizing plate with excellent interlayer adhesion even though the first protective film 11 and the second protective film 15 have low moisture permeability as described above. Furthermore, according to the manufacturing method of the present invention, it is possible to obtain a polarizing plate with superior appearance quality compared to when an ultraviolet-curing adhesive is used.

[0073] The method for manufacturing a polarizing plate according to the present invention will be described with reference to Figure 2. In the first step, a first protective film 21 and a polarizer 23 are bonded together via a first aqueous adhesive layer 22 to obtain a laminate 24 [Figure 2(a)]. The first aqueous adhesive layer 22 can be manufactured as described above. In the first step, one side of the polarizer is open and moisture can easily escape, so the first aqueous adhesive layer 22 tends to be easily obtained.

[0074] If the polarizer 23 is a stretched film or stretched layer on which a dye having absorption anisotropy is adsorbed, the polarizer 23 can be manufactured as described in the above-mentioned description of the stretched film or stretched layer on which a dye having absorption anisotropy is adsorbed.

[0075] If the polarizer 23 is a film coated with and cured with the above-mentioned absorption anisotropy dye, the polarizer 23 can be formed on a base film via an alignment film. The polarizer 23 can be formed by coating and curing a polarizer-forming composition containing a dichroic dye and a polymerizable liquid crystal compound. In addition to the above-mentioned dichroic dye and polymerizable liquid crystal compound, the polarizer-forming composition preferably further contains a polymerization initiator, a leveling agent, and a solvent, and may further contain a photosensitizer, a polymerization inhibitor, a leveling agent, etc.

[0076] The coating, drying, and polymerization of the polarizer-forming composition and polymerizable liquid crystal compound can be carried out by conventionally known coating, drying, and polymerization methods. For example, the coating method for the polarizer-forming composition can include wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, and die coating.

[0077] The polymerization method for polymerizable liquid crystal compounds can be selected according to the type of polymerizable group in the polymerizable liquid crystal compound. If the polymerizable group is a photopolymerizable group, polymerization can be performed by photopolymerization. If the polymerizable group is a thermopolymerizable group, polymerization can be performed by thermopolymerization. In the present invention, photopolymerization is preferred. Photopolymerization does not necessarily require heating the substrate film to a high temperature, so a substrate film with low heat resistance can be used. Photopolymerization is performed by irradiating a film made of a polarizer-forming composition containing a polymerizable liquid crystal compound with visible light or ultraviolet light. Ultraviolet light is preferred because it is easier to handle.

[0078] In the second step, a water-based adhesive coating 25 is formed on the polarizer 23 side of the laminate 24 [Figure 2(b)]. The method for forming the water-based adhesive coating 25 on the polarizer 23 can be carried out by a conventionally known method.

[0079] In the third step, the water-based adhesive coating 25 is dried to form a second water-based adhesive layer 26 [Figure 2(c)]. The third step may further include a step of laminating a release film 27 onto the water-based adhesive coating 25 [Figure 2(c1)], and a step of peeling off the release film 27 after the water-based adhesive coating 25 has been dried to form the second water-based adhesive layer 26 [Figure 2(c2)]. The method for drying the water-based adhesive coating 25 can be, for example, a conventionally known method. The drying temperature of the water-based adhesive coating 25 may be, for example, 20°C to 90°C. The drying time of the water-based adhesive coating 25 may be, for example, 1 minute to 60 minutes.

[0080] The release film 27 is preferably composed of a plastic film and a release layer. In the third step, when drying the water-based adhesive, the plastic film used should have a moisture permeability of 200 g / m², from the viewpoint of sufficiently removing moisture from the adhesive. 2 It is preferable that the exposure time is 24 hours or more. Examples of plastic films include triacetylcellulose resin (TAC) films. The release layer can be formed from, for example, a release layer forming composition. The main components (resins) constituting the release layer forming composition are not particularly limited, but examples include silicone resins, alkyd resins, acrylic resins, and long-chain alkyl resins.

[0081] In the fourth step, a surface activation treatment is applied to the surface of the second aqueous adhesive layer 26 opposite to the polarizer 23 side, and then the laminate 24 and the second protective film 28 are bonded together via the second aqueous adhesive layer 26 to obtain a polarizing plate 20 [Figure 2(d)]. The fourth step includes a step of applying a surface activation treatment to the surface of the second aqueous adhesive layer 26 opposite to the polarizer 23 side before bonding the laminate 24 and the second protective film 28, in order to facilitate the adhesion between the second aqueous adhesive layer 26 and the second protective film 28 of the polarizing plate [Figure 2(d1)]. Examples of surface activation treatments include dry treatments such as corona treatment, plasma treatment, discharge treatment (glow discharge treatment, etc.), ozone treatment, UV ozone treatment, and ionizing ray treatment (ultraviolet treatment, electron beam treatment, etc.). These surface activation treatments may be performed individually or in combination of two or more. Among these, corona treatment is preferred. Corona treatment is, for example, 1 kJ / m 2 More than 50kJ / m 2 The following output can be produced. The time required for corona processing may be, for example, between 1 second and 1 minute.

[0082] Although not shown in the figures, the method for manufacturing a polarizing plate of the present invention may further include a curing step after the fourth step to facilitate improving the adhesion between the second adhesive layer 26 and the second protective film 28 of the polarizing plate 20. In the curing step, the polarizing plate may be heated. In the curing step, the temperature at which the polarizing plate 20 is cured may be, for example, 20°C or more and 90°C or less, preferably 40°C or more and 90°C or less, more preferably 60°C or more and 90°C or less, and particularly preferably 75°C or more and 85°C or less. In the curing step, the curing time for the polarizing plate 20 may be, for example, 1 minute or more and 2 hours or less.

[0083] The polarizing plate 20 obtained by the manufacturing method of the present invention may have an adhesion force between the second aqueous adhesive layer 26 and the second protective film 28 of, for example, 0.3 N / 25 mm or more, preferably 0.5 N / 25 mm or more, and more preferably 1 N / 25 mm or more. The polarizing plate 20 may have an adhesion force between the second aqueous adhesive layer 26 and the second protective film 28 of, for example, 20 N / 25 mm or less, and may be, for example, 15 N / 25 mm or less or 10 N / 25 mm or less. The polarizing plate 20 may have an adhesion force between the first aqueous adhesive layer 22 and the first protective film 21 of, for, 0.1 N / 25 mm or more and 20 N / 25 mm or less. [Examples]

[0084] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" refer to mass%, and parts, respectively, unless otherwise specified.

[0085] (Measurement of moisture permeability) Using a constant temperature and humidity chamber, the water vapor transmission rate was measured under the following conditions: temperature 40°C, relative humidity 90%RH, and measurement time 24 hours, using the water vapor transmission rate test method (cup method, in accordance with JIS Z 0208). The measured water vapor transmission rate was expressed as the water vapor transmission rate [g / m³] at 40°C and 90%RH. 2 [24hr]

[0086] (Measurement of thickness) The layer thickness was measured using a contact-type film thickness measuring device (Nikon Corporation "MS-5C"). The thickness of the water-based adhesive layer and the polarizer was measured using a laser microscope (Olympus Corporation "OLS3000").

[0087] (Evaluation of adhesion strength) A polarizing plate was cut to a width of 25 mm to obtain a measurement sample. Using the Shimadzu Corporation's precision universal testing machine "Autograph AGS-50NX," the second protective film side of the measurement sample was attached to a glass plate via adhesive. The adhesion force was measured by grasping the measurement sample from the first protective film to the second adhesive layer and measuring the force required to peel it off in a 180° direction. The measurement was performed at a peeling speed of 300 mm / min, a temperature of 23 ± 2°C, and a relative humidity of 50 ± 5%. The results of the adhesion force measurement are shown in Table 1. In the table, "○" indicates material failure of the measurement sample, and "×" indicates that peeling of the measurement sample occurred before measurement and the adhesion force could not be evaluated.

[0088] (Measurement of light transmittance) The protective film was cut to a size of 30 mm x 30 mm, and the transmittance [%] was measured between wavelengths of 200 and 510 nm. A UV-Vis spectrophotometer "UV-2450" manufactured by Shimadzu Corporation was used for the measurements.

[0089] (Evaluation of surface irregularities of polarizing plates by measuring reflectivity) The reflective clarity of the polarizing plate was measured as follows. First, a polarizing plate was cut to a size of 100 mm x 100 mm and used as the evaluation sample. The first protective film side of this evaluation sample was bonded to a black acrylic plate via a transparent adhesive layer. For the evaluation sample bonded to the black acrylic plate described above, the reflection clarity (%) was determined by irradiating the surface of the evaluation sample with light from a light source at an incident angle of 45° using the "ICM-1T" image clarity measuring instrument manufactured by Suga Test Instruments Co., Ltd., in accordance with the "reflection method" section of JIS K 7374 [Plastics - Method for determining image clarity]. The width of the optical comb was set to 0.125 mm. The evaluation sample was positioned so that the direction of the absorption axis of its polarizer layer was parallel to the plane containing the incident light and detected reflected light. The higher the flatness of the surface of the evaluation sample, the higher the reflection clarity. Regarding the measurement results, "○" indicates a reflectivity of 5% or higher, "×" indicates a reflectivity of less than 5%, and "-" indicates that the adhesion between the polarizer and the protective film was insufficient and the reflectivity could not be measured. The results are shown in Table 1.

[0090] (Manufacturing Example 1: Fabrication of a polarizer) A polyvinyl alcohol film with an average degree of polymerization of approximately 2400, a degree of saponification of 99.9 mol% or more, and a thickness of 30 μm was immersed in pure water at 30°C, and then iodine-stained by immersion in an aqueous solution at 30°C with a mass ratio of iodine:potassium iodide:water of 0.02:2:100 (hereinafter also referred to as the iodine staining process). The polyvinyl alcohol film that had undergone the iodine staining process was then immersed in an aqueous solution at 56.5°C with a mass ratio of potassium iodide:boric acid:water of 12:5:100 (hereinafter also referred to as the boric acid treatment process). After the boric acid treatment process, the polyvinyl alcohol film was washed with pure water at 8°C and then dried at 65°C to obtain a polarizer (thickness after stretching) in which iodine was adsorbed and oriented on the polyvinyl alcohol. During this process, stretching was performed in both the iodine staining process and the boric acid treatment process. The total extension ratio in this extension was 5.3 times.

[0091] (Manufacturing Example 2: Preparation of Water-Based Adhesive 1) A water-based adhesive was obtained by adding 3 parts by mass of polyvinyl alcohol-based resin to 100 parts by mass of water and stirring and mixing.

[0092] (Manufacturing Example 3: Preparation of Water-Based Adhesive 2) A water-based adhesive was obtained by adding 4.5 parts by mass of polyvinyl alcohol-based resin to 100 parts by mass of water and stirring and mixing.

[0093] <Example 1> A water-based adhesive 1 is applied to one side of the polarizer, and a first protective film [moisture permeability 6g / m²] is applied to the other side of the polarizer. 2 • 24hr, light transmittance of 5% at a wavelength of 380nm, manufactured by Zeon Corporation, cyclic polyolefin resin (COP) film "Zeonor ZF14" containing UV absorber, thickness 52μm, at 14kJ / m² 2After corona treatment, the layers were bonded together to obtain a laminate having a layer structure of a first protective film, a first aqueous adhesive layer (thickness 0.1 μm), and a polarizer. Next, a water-based adhesive 1 was applied to the surface of the polarizer opposite to the first protective film, forming a coating of the water-based adhesive. Subsequently, a release film [a triacetylcellulose resin (TAC) film with a release treatment, 25 μm thick] was laminated onto the water-based adhesive 1 coating, dried for 5 minutes in an atmospheric environment at 80°C, and then the release film was peeled off to obtain a second water-based adhesive layer with a thickness of 0.1 μm. For the second water-based adhesive layer, 14 kJ / m 2 After corona treatment, a second protective film [moisture permeability 13g / m²] is applied. 2 • 24hr, light transmittance of 6% at a wavelength of 380nm, manufactured by Zeon Corporation, cyclic polyolefin resin (COP) film "Zeonor ZF12" containing UV absorber, thickness 13μm, at 14kJ / m² 2 After corona treatment, the layers were bonded together to obtain a polarizing plate having a layer structure of a first protective film / first aqueous adhesive layer / polarizer / second aqueous adhesive layer / second protective film. The results are shown in Table 1. Figure 3 shows the reflected image of the polarizing plate of Example 1 when a fluorescent lamp was projected onto its surface. The sample used was the evaluation sample used when measuring the clarity of reflection. As shown in Figure 3, the surface of the polarizing plate of Example 1 was smooth and the appearance quality was good.

[0094] <Example 2> Polarizing plates were prepared in the same manner as in Example 1. The prepared polarizing plates were subjected to a curing process in which they were heated for 10 minutes in an atmospheric environment at a temperature of 40°C. The adhesion strength of the polarizing plates after drying was measured. The results are shown in Table 1.

[0095] <Examples 3-20> A polarizing plate was prepared in the same manner as in Example 1, except that the corona treatment conditions for the water-based adhesive and the second water-based adhesive layer shown in Table 1 were used. When performing the curing process, the curing process was carried out in the same manner as in Example 2, except that the curing conditions shown in Table 1 were used. The results are shown in Table 1.

[0096] <Comparative Examples 1-3> A polarizing plate was prepared in the same manner as in Example 1, except that corona treatment was not performed on the second aqueous adhesive layer. When performing the curing process, the curing process was carried out in the same manner as in Example 2, except that the curing conditions were as shown in Table 1. The results are shown in Table 1. The second aqueous adhesive layer and the second protective film were not bonded together.

[0097] <Comparative Examples 4-6> A polarizing plate was prepared in the same manner as in Example 1, except that a water-based adhesive 1 was applied to the surface of the polarizer opposite to the first protective film side to form a coating of water-based adhesive 1, a second protective film was laminated on the coating, and the polarizing plate was obtained after drying for 5 minutes in an atmospheric atmosphere at a temperature of 80°C. The curing process was carried out in the same manner as in Example 2, except that the curing conditions were as shown in Table 1. The results are shown in Table 1.

[0098] <Comparative Example 7> A polarizing plate was fabricated in the same manner as in Example 1, except that the polarizer surface was subjected to corona treatment without forming a second adhesive layer, and a second protective film was laminated. The results are shown in Table 1.

[0099] <Comparative Example 8> A water-based adhesive 1 was applied to one side of the polarizer. A first protective film (moisture permeability 6 g / m²) was applied to one side of the polarizer via the water-based adhesive 1. 2 A cyclic polyolefin resin (COP) film "Zeonor ZF14" (manufactured by Zeon Corporation, 52 μm thick) with a light transmittance of 5% at a wavelength of 380 nm was laminated to the first protective film. Before lamination, 14 kJ / m² was applied to the lamination surface of the first protective film. 2 Corona treatment was performed under the specified conditions. A laminate was obtained having a layer structure of a first protective film / first aqueous adhesive layer (thickness 0.1 μm) / polarizer. A UV-curing adhesive was applied to the surface of the polarizer opposite to the first protective film side. A second protective film (moisture permeability 13g / m²) was placed on top of the UV-curing adhesive. 2A cyclic polyolefin resin (COP) film "Zeonor ZF12" (manufactured by Zeon Corporation, with a UV absorber, 13 μm thick) with a light transmittance of 6% at a wavelength of 380 nm over 24 hours was laminated. Before lamination, 14 kJ / m² was applied to the bonding surface of the second protective film. 2 Corona treatment was performed under the specified conditions. Subsequently, ultraviolet light was irradiated from the side of the second protective film to cure the ultraviolet-curable adhesive. A polarizing plate was obtained having a layer structure of first protective film / first water-based adhesive layer / polarizer / ultraviolet-curable adhesive layer / second protective film. The results are shown in Table 2.

[0100] <Comparative Example 9> The second protective film (moisture permeability 13g / m²) 2 A polarizing plate was prepared in the same manner as in Comparative Example 8, except that it was a cyclic polyolefin resin (COP) film "Zeonor ZF12" manufactured by Zeon, with a light transmittance of 90% at a wavelength of 380 nm, and a thickness of 13 μm, after 24 hours of testing. The results are shown in Table 2. Figure 4 shows the reflected image of the polarizing plate of Comparative Example 9 when a fluorescent lamp was projected onto its surface. The sample used was the evaluation sample used when measuring the clarity of the reflection. As shown in Figure 4, the protective film of the polarizing plate of Comparative Example 9 shrunk and wrinkled.

[0101] [Table 1] In the table, "-" indicates that the processing or measurement was not performed.

[0102] [Table 2] In the table, "-" indicates that the processing or measurement was not performed. [Explanation of Symbols]

[0103] 10,20 Polarizing plate, 11,21 First protective film, 12,22 First water-based adhesive layer, 13,23 Polarizer, 14,26 Second water-based adhesive layer, 15,28 Second protective film, 24 Laminate, 25 Water-based adhesive coating, 27 Release film.

Claims

1. A first step involves bonding a first protective film and a polarizer via a first aqueous adhesive layer to obtain a laminate, A second step of forming a water-based adhesive coating on the polarizer of the laminate, A third step involves drying the coating film of the aforementioned water-based adhesive to form a second water-based adhesive layer, A fourth step involves applying a surface activation treatment to the surface of the second aqueous adhesive layer opposite to the polarizer side, and then bonding the laminate and the second protective film via the second aqueous adhesive layer. They are provided in this order, The moisture permeability of both the first and second protective films at a temperature of 40°C and a relative humidity of 90% RH is 200 g / m². 2 - Less than 24 hours The aforementioned surface activation treatment is corona treatment. The aforementioned corona treatment was 14 kJ / m³ 2 50kJ / m or more 2 The following output was produced: The third step is, A step of laminating a release film onto the coating film of the water-based adhesive, After drying the coating film of the water-based adhesive layer, the process involves peeling off the release film. Furthermore, The moisture permeability of the aforementioned release film at a temperature of 40°C and a relative humidity of 90% RH is 200 g / m². 2 A method for manufacturing polarizing plates, with a lifespan of 24 hours or more.

2. The method for manufacturing a polarizing plate according to claim 1, further comprising a curing step of heating the polarizing plate after the fourth step.

Citation Information

Patent Citations

  • Preparation of deflecting plate

    JP1979163051A

  • Polarizing plate protective film and polarizing plate

    JP2000206303A

  • Laminate and method for manufacturing the same

    JP2003211589A

  • Polarizing plate and manufacturing method therefor

    JP2005043858A

  • Polarizing plate

    JP2007127892A